Pressure distribution in small hydrodynamic journal bearings considering cavitation: a numerical approach based on the open‐source CFD code OpenFOAM®. (24th February 2016) - Concli, Franco
Abstract: Hydrodynamic journal bearings are traditionally designed using the half‐Sommerfeld theory. This consists in a semi‐analytical solution of the continuity and momentum conservation equations substituting negative pressures with the ambient pressure. This hypothesis provides acceptable results, but a better understanding of the phenomena considering the effective pressure distribution including 3D and cavitation effects can be achieved only by using numerical methods. For this reason, some different solvers and cavitation models were applied to different geometries for which literature provides experimental data. Once the numerical model was validated, a parametric analysis was performed in order to better understand the influence of the rotational speed and the relative eccentricity on the attitude angle, the reaction forces, the pressure distribution and the power losses of a small journal bearing. Copyright © 2016 John Wiley & Sons, Ltd.